National reality and future determinants of telemedicine use - Hassam, Inaara Salim (2022)
Firstly described in 1970, telemedicine is perceived as a way to receive care of health in distance. The COVID-19 pandemic has created the need for implementation of telemedicine services in order to provide safer healthcare options. Perception and satisfaction with telemedicine are linked factors to the use of these systems and understanding a population’s current perspective of telemedicine can ensure their satisfaction now, and in the future. In our primary study, by investigating current telemedicine implementation in Portugal through informal interviews, results have shown that we currently face many obstacles in education and training of telemedicine, leading to poor use and satisfaction with the systems. Through our second study, we statistically assess possible affecting factors to the relationship between these two variables, such as the quality of the interface and interaction, trust in the system, and self-efficacy in using these technologies. This study has created a basic correlation structure for perception-based factors impacting satisfaction, making it a valuable asset to consider when building or creating tools for ensuring acceptance and future use of this service.